Modern principles of pharmaceutical treatment in patients with chronic coronary heart disease - S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика, 2008)
The article is devoted to general principles of chronic coronary heart disease treatment, according to modern international guidelines. Information on medications improving life prognosis and/or clinical symptoms is presented.